Atomic oxygen erosion resistance of polyimides filled hybrid nanoparticles. (April 2020) - Andropova, Ulyana; Serenko, Olga; Tebeneva, Nadezhda; Tarasenkov, Aleksander; Buzin, Mihail; Afanasyev, Egor; Sapozhnikov, Dmitriy; Bukalov, Sergey; Leites, Larisa; Aysin, Rinat; Polezhaev, Aleksander; Naumkin, Aleksander; et al.
Abstract: In this paper, a new kind of space-durable nanocomposites has been prepared using one-step in situ method of filling organosoluble polyimides (PI). Three types of metalloalkoxysiloxanes (tris-(diethoxymethylsiloxy) aluminum, tetrakis-(diethoxymethylsiloxy) zirconium, pentakis-(diethoxymethylsiloxy) niobium) were used as filler precursors. It is demonstrated that the nanosized filler particles formed in the polymer volume have a hybrid chemical structure and contain М-О-Si and Si–O–Si bonds. The in situ filling of PI preserves its unique thermal properties, increases the glass transition temperature, and maintains high stability to the thermal oxidation of the matrix PI. The atomic oxygen (AO) erosion resistance of the filled PI has been investigated by exposing its surface to a variety of AO fluences. The introduction of nanosized filler in PI contributes to a sharp, order-of-magnitude decrease in the AO erosion coefficient of the nanocomposite. The valence of the central metal atom of the precursor predetermines the silica-block content in the forming filler and its atomic oxygen AO-protective function. During the transition from a precursor with a trivalent metal atom to a precursor with a tetra- or pentavalent metal atom, the erosion coefficient of filled PI decreases at a constant fluence of AO. Taking into account that the M-O bond energy in a M-O-Si group is higher than the Si–O bond energy, the presence of such atoms as Zr or Nb in the chemical structure of the filler can act as a "reinforcing" element that increases the resistance of the protective layer against AO action. Graphical abstract: Image 1 Highlights: The use metalloalkoxysiloxanes as precursors simplifies preparation of filled polyimides (PI). Nanoparticles formed in the polymer contain metallosiloxane and silica blocks. The introduction of hybrid nanoparticles in PI offer its excellent AO erosion resistance. The valence of the metal atom of precursors predetermines AO-protective properties of PI films. In situ filling of polyimides preserves their unique thermal properties.